Direcionamentos da tecnologia industrial de células a combustível de óxidos sólidos Directions of the industrial development of the solid oxide fuel cells technology - Daniel Z. de Florio; José A. Varela; Fabio C. Fonseca; Eliana N. S. Muccillo; Reginaldo Muccillo (Química Nova, 2007)
This manuscript shows an overview of the solid oxide fuel cell (SOFC) technology based on industrial developments. The information presented has been collected mostly at conferences that the authors attended. It is observed that several companies have been pursuing the development of the SOFC technology. Significant advances in stability and power density have raised the economic interest in this technology recently. It is revealed that the SOFC materials are essentially the same ones that have been used in the past decades, and that the two most important designs of pre-commercial SOFC prototypes are the tubular and planar ones.